ChemInform Abstract: Synthesis of Furoxans (1, 2, 5‐Oxadiazole 2‐oxides) from Styrenes and Nitrosonium Tetrafluoroborate in Non‐Acidic Media and Mechanistic Study. Issue 51 (5th December 2016) - Matsubara, Ryosuke; Ando, Akihiro; Saeki, Yuta; Eda, Kazuo; Asada, Naoki; Tsutsumi, Tomoaki; Shin, Yong Soon; Hayashi, Masahiko
Abstract: The products are obtained as a mixture of two regioisomers with the furoxan bearing an external N‐oxygen atom at the distal side from the aryl substituent being the major product.